Carbonaceous aerosol variability and SOA formation during foggy days in Delhi, India - Sonwani, Saurabh; Saxena, Pallavi; Srivastava, Anju (Frontiers in Sustainable Cities, 2022)
The variability of organic carbon (OC), elemental carbon (EC), and secondary organic aerosol (SOA) and their relationship with meteorological parameters have been studied during foggy and non-foggy days in the peak winter months (December-January) during the period of 2015-16 inDelhi, India. Different sectoral locations were chosen on the basis of pre-dominant industrial, traffic, and residential activities with a background location. The average level of OC, EC and SOA were found to be 7.47±7.74 μg/m3, 0.69± 0.7 μg/m3 and 10.46±10.76 μg/m3 respectively during the foggy period and 6.1± 6.8 μg/m3, 0.9±1.1 μg/m3, and 9.1± 10.6 μg/m3 respectively during the non-foggy period in Delhi. A relatively higher SOA level was observed at industrial and traffic intersection site, which indicate the proximity of the dominant source of OC that play a significant role in SOA formation. It was also found that, SOA production associated with the OC/EC ratio and may vary from site to site. Correlation analysis has confirmed that OC is having a significant strong positive correlation with EC and SOA while EC is showing a significant moderate positive correlation with SOA. Ambient temperature (AT) shows a significant negative moderate correlation with OC levels and SOA and formation. Due to hydrophilicity (hydrophobicity) of OC (EC), its average concentration was found high (less) due to its high (less) scavenging during foggy days in comparison to non-foggy days. The study further suggests the significant impact of source variability on SOA formation due to the different nature of sector-wise sites during foggy days in Delhi.